Citric acid as feed additive in diet of rabbit- effect on growth performance (Journal of the Bangladesh Agricultural University, 2014)
The experiment was conducted for a period of 56 days using 24 growing rabbits (4 to 6 weeks old) to evaluate the effect of citric acid (CA) on the growth performance. Concentrate mixture was fortified by 0, 0.5, 1.0 and 1.5% CA to 4 different groups of rabbit considering 6 in each. Green grass and concentrate mixture were supplied on ad-libitum basis. Growth rate increased 5, 8 and 12% respectively in 0.5, 1.0 and 1.5% CA supplemented groups (P>0.05). Total dry matter (DM) intake decreased numerically due to increased level of CA whereas, growth velocity increased with increased level of CA. Insignificant difference observed in terms of feed conversion ratio (FCR-DM intake/weight gain) among different groups but improved 6, 16, and 8 % respectively in 0.5, 1.0 and 1.5% CA offering groups. Over all numerically better performance obtained due to addition of CA in rabbit diet. So, it may be concluded that the CA up to level of 1.5% in diet may have positive effect on growth performance of growing rabbit. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21246 J. Bangladesh Agril. Univ. 12(1): 87-90, June 2014